2017
DOI: 10.1159/000481610
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4/Let-7a Axis Regulates Metastasis and Chemoresistance of Pancreatic Cancer Cells Through Targeting HMGA2

Abstract: Background/Aims: Pancreatic cancer cells (PCC) is one of the most risky cancers and gemcitabine (GEM) is the standard first-line drug for treating PCC. The PCC will develop drug resistance to GEM after a period of treatment. However, the detailed molecular mechanism of pathogenesis and drug resistance remains unresolved. Methods: we employed qRT-PCR and western blot to examine the expression level of CXCR4, let-7a and HMGA2. In addition, we used MTT assay to detect cell proliferation and transwell assay to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…regulates ACPA-induced macrophage activation in RA, which leads to worse treatment outcome 35 ; (b) let-7a-5p might affect sensitivity to treatment drugs, resulting in lower clinical response. 36 In addition, we also found that CRP independently predicted higher clinical response, while biologics history independently predicted lower clinical response to TNF inhibitor in RA patients. These might result from that: (a) high CRP is correlated with high inflammation which would benefit more from anti-inflammation treatment, and it has been demonstrated in several studies that high CRP could predict clinical response to DMARDs, TNF inhibitor, and other biologics 37,38 ; and (b) as to patients with biologics history, they are easy to produce anti-antibody when they use biologics again, which could induce secondary resistance, thereby decreasing the efficacy of treatment.…”
Section: Discussionsupporting
confidence: 54%
“…regulates ACPA-induced macrophage activation in RA, which leads to worse treatment outcome 35 ; (b) let-7a-5p might affect sensitivity to treatment drugs, resulting in lower clinical response. 36 In addition, we also found that CRP independently predicted higher clinical response, while biologics history independently predicted lower clinical response to TNF inhibitor in RA patients. These might result from that: (a) high CRP is correlated with high inflammation which would benefit more from anti-inflammation treatment, and it has been demonstrated in several studies that high CRP could predict clinical response to DMARDs, TNF inhibitor, and other biologics 37,38 ; and (b) as to patients with biologics history, they are easy to produce anti-antibody when they use biologics again, which could induce secondary resistance, thereby decreasing the efficacy of treatment.…”
Section: Discussionsupporting
confidence: 54%
“…The altered expression of let-7a could increase chemoresistance to epirubicin (214) and cytarabine (215). Furthermore, let-7a expression has demonstrated to influence chemoresistance, due to maintained treatment with gemcitabine, in pancreatic cancer patients (216, 217). Several studies have reported that let-7a acts as a tumor suppressor in renal cell carcinoma (RCC), by targeting c-Myc (218).…”
Section: A Network Analysis: the Most Central Ncrnas In Chemoresistancementioning
confidence: 99%
“…Let-7 expression has been shown to have prognostic value in many tumours [53,70,200,201,285]. Moreover, the evaluation of let-7 family member expression in body fluids (plasma, serum, urine, and stool) has demonstrated utility in the early detection of tumours, as a prognostic tool [284] and as a chemoresistance predictor [205]. The downregulation of let-7a-5p in serum has been shown to predict lymph node metastasis and prognosis in colorectal cancer patients [286], whereas the RKIP/let-7 pathway metastasis signature has been demonstrated to predict a high risk of metastasis in breast cancer with higher accuracy than the individual genes [287].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to HMGA2 truncation, a decrease in let-7 expression can be solely responsible for the increased expression of otherwise normal HMGA2 or HMGA1 [51] in several different cancers, such as breast [69], gastric [70] and non-small cell lung cancers [63], sarcomas [197,198], hepatocellular carcinomas, nasopharyngeal [72] and oesophageal squamous cell carcinomas [199], uterine leiomyomas and leiomyosarcomas [66,200], and pituitary adenomas [201], as a loss of let-7 expression is a marker for less well-differentiated cancers [46]. Moreover, a role for let-7/HMGA in epithelial-mesenchymal transition (EMT), cell migration, and metastasis has been demonstrated in several cancers and cellular systems [51,72,[202][203][204][205].…”
Section: The Lin28/let-7 Axismentioning
confidence: 99%